ANALYSIS OF THE CONFORMITY OF CARBON EMISSION DISCLOSURE BASED ON ENVIRONMENTAL MANAGEMENT ACCOUNTING THROUGH GRI 305 IN IDX LQ45 LOW CARBON LEADER INDEX COMPANIES (2022–2024) - Tyas Aswadina Poliyama; Mahdalena Mahdalena; Ronald S. Badu (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the level of conformity of carbon emission disclosure based on Environmental Management Accounting (EMA) through the GRI 305 standard in companies included in the IDX LQ45 Low Carbon Leaders (LQ45LCL) index during the period 2022–2024. The increasing global attention to Environmental, Social, and Governance (ESG) issues encourages companies to improve transparency in environmental reporting, particularly regarding carbon emissions. EMA plays an important role as an internal accounting system that provides environmental information used in sustainability reporting. However, variations in the quality of carbon emission disclosure among companies indicate that the implementation of EMA is not yet fully optimal. This research uses a quantitative descriptive approach by analyzing the level of disclosure conformity of GRI 305 indicators in sustainability reports of companies included in the IDX LQ45 Low Carbon Leaders index. The level of conformity is calculated by comparing the number of disclosed indicator criteria with the maximum number of criteria that should be disclosed. The classification of disclosure levels includes not applied, limited disclosure, partially applied, well applied, and fully applied. The results show that the level of carbon emission disclosure among companies varies across the observation period. Several companies demonstrate an increasing trend in disclosure, while others experience fluctuations or remain at a limited disclosure level. Overall, most companies fall within the partially applied category, indicating that carbon emission disclosure has not yet been comprehensively implemented according to the GRI 305 standards. These findings suggest that although companies in the LQ45LCL index are recognized as low-carbon leaders, improvements in the implementation of Environmental Management Accounting are still needed to enhance the transparency and completeness of carbon emission reporting.